2008
DOI: 10.1016/j.ejphar.2008.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Expression of BMP7 is associated with resistance to diabetic stress: Comparison among mouse salivary glands

Abstract: We determined mRNA levels of bone morphogenetic protein 7 (BMP7), a growth and differentiation factor belonging to the transforming growth factor-β superfamily, in the salivary glands of mice with streptozotocin (200 mg/kg, i.p.)-induced diabetes. We also examined the effects of BMP7 on secretion of saliva and degenerative change in salivary glands in diabetic mice. In normal mice, BMP7 mRNA levels were high in the submandibular gland and low in the parotid gland, while in diabetic mice, levels were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Saliva was pipetted directly from the mouth and collected in pre‐weighed Eppendorf tubes. Saliva volume was determined gravimetrically, assuming a density of 1 g/ml of saliva (16), and flow rates (μl/min/100 g body weight) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Saliva was pipetted directly from the mouth and collected in pre‐weighed Eppendorf tubes. Saliva volume was determined gravimetrically, assuming a density of 1 g/ml of saliva (16), and flow rates (μl/min/100 g body weight) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Bone morphogenetic protein 7 (BMP7) is a protein in the transforming growth factor β superfamily, which has a multifunctional role in the control of cell proliferation, differentiation, growth and apoptosis (Cecchi et al 2016 ). It has been shown that high levels of BMP7 mRNA play a significant role in secretory and degenerative changes in salivary glands in DM mice (Izumi et al 2008 ). Reduced BMP7 levels in the parotid, but not submandibular gland, were associated with DM, Table 1 .…”
Section: Salivary Gland Diseases and Diabetes Mellitusmentioning
confidence: 99%
“…Reduced BMP7 levels in the parotid, but not submandibular gland, were associated with DM, Table 1 . Histologically, remarkable degeneration with atrophy was also found in parotid gland, while degeneration of submandibular gland was insignificant (Izumi et al 2008 ). To check if this is reversible with BMP7 therapy, BMP7 (50 and 100 µg/kg, i.v.)…”
Section: Salivary Gland Diseases and Diabetes Mellitusmentioning
confidence: 99%
“…BMP7 is expressed in specific types of normal mature tissue, representatively the kidney [87,88]. BMP7 mRNA expression is seen in mature murine salivary gland tissue [89]. In contrast to normal tissue of rats, BMP7 and its receptors disappeared in interstitial fibrosis of diabetic nephropathy [90].…”
Section: Tgf-β Signaling In Fibrosismentioning
confidence: 99%